Empowering Sustainable Behavior Among Universiti Utara Malaysia (UUM) Community Through Electric Pedal-Assisted Bicycles (EPAB) - Ramely, Asmahany; Ab. Talib, Mohd Fadzilillah; Mokhtar, Muhammad Fauzi; Rashid Radha, Jasmine Zea Raziah Radha (UUM, 2022)
Sustainable behaviour is considered as one of the ecological behaviours contributing to environmental preservation and/or conservation because it is highly encouraging people to limit non-renewable material and energy resources. In the Universiti Utara Malaysia (UUM), the sustainable behaviour among among its community is relatively common. This can be seen through their daily environmentally-friendly practice such as energy and water conservation, green mobility, and cycling. A majority of the UUM community think that attitude towards ecological behaviour, social pressure, and the easiness to perform ecological behaviour are contributing factors to their sustainable behaviour. Theoretically, this situation can be explained by the Theory of Planned Behavior (TPB), whereby attitude, subjective norms, and perceived behavioural control determine an individual's behaviour. Regarding the use of electric pedal-assisted bicycles (EPAB) as an indicator of sustainable behaviour, most respondents stated that their peers’ review about EPAB influenced their use of EPAB. It was the the ease of using EPAB, such as the flexibility of EPAB rental policy and procedures under the management of BSD, that influenced the active use of EPAB. The finding of this study validates all of the greening efforts made by UUM. It also gives more value to UUM as one of the universities that have secured a good rank in UI GreenMetric. More importantly, UUM's effort to encourage sustainable behaviour among its community aligns with the Kedah State Green Agenda and supports the Sustainable Development Goals (SDG) 2030.